Pengaruh Pengetahuan Investasi, Motivasi Investasi dan Preferensi Risiko Terhadap Minat Investasi - Rokhim, Yusril Atiqur; Wibowo, Purwo Adi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The aim of carrying out this study by researchers is to find out what influence investment knowledge, investment motivation and risk preferences have on investment interest in the millennial generation in Jepara Regency. The research was conducted using a quantitative approach accompanied by survey methods. The technique for collecting data used a questionnaire distributed to 103 millennial generation respondents in Jepara, with sampling using the purposive sampling method. Analysis of the data obtained was carried out using multiple linear regression analysis assisted by IBM SPSS Statistics 25 software. The results of this research show that the t-value of the investment knowledge variable is 2.909, exceeding the t-table (1.984) with p-value = 0.004, so it can be concluded that Investment Knowledge has a significant influence on Investment Interest. Furthermore, the t value obtained from the investment motivation variable is 2.492, exceeding the t-table with p-value = 0.014, so that Investment Motivation has a significant influence on investment interest. Risk preference obtained a value of t = 2.789 which exceeds the t-table and p-value = 0.006, so it can be concluded that risk preference has a significant influence on investment interest. After carrying out this research, researchers found that investment knowledge, investment motivation and risk preferences had a significant influence on investment interest in the millennial generation in Jepara Regency, both individually and collectively.